2011
DOI: 10.1002/acr.20539
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatologists on the road: A subspecialist's role in caring for the homebound

Abstract: Objective. By 2030, the number of permanently homebound individuals in the US will increase by 50% to reach 2 million. However, no medicine subspecialty consult services exist for this rising subset of the population. This pilot program establishes a rheumatology consult service for the Mount Sinai Visiting Doctors, the largest primary care academic home visit program in the nation serving more than 1,000 patients in New York City. Our service addresses the unmet need for homebound patients with rheumatic dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Participants also reported that video visits improved efficiency by allowing them to triage patients’ needs quickly and determine when in-person care was needed, for example, during an urgent care visit. Eliminating travel time allowed providers to schedule more visits, a critical benefit when many practices were short-staffed due to redeployments and illness, and improved access to specialists, a particular concern for the homebound population (Jain et al, 2011). The ability to expand capacity through video encounters could be a valuable asset for HBPC practices that are often financially challenged (Desai et al, 2008; Eric De Jonge et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Participants also reported that video visits improved efficiency by allowing them to triage patients’ needs quickly and determine when in-person care was needed, for example, during an urgent care visit. Eliminating travel time allowed providers to schedule more visits, a critical benefit when many practices were short-staffed due to redeployments and illness, and improved access to specialists, a particular concern for the homebound population (Jain et al, 2011). The ability to expand capacity through video encounters could be a valuable asset for HBPC practices that are often financially challenged (Desai et al, 2008; Eric De Jonge et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Pilot models are needed to provide at least recognition of need for care for community‐dwelling homebound individuals effectively and efficiently, ideally in collaboration with the medical care being provided in the home given their debility. Prior work has shown the feasibility of specialty consultation services embedded in a home‐based primary care program . Given the current scarcity of in‐home dental care services and dental professionals providing home‐based dentistry, it may be more feasible to begin a referral‐based pilot of home‐based dental services within an established primary care program.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has shown the feasibility of specialty consultation services embedded in a home-based primary care program. 29 Given the current scarcity of in-home dental care services and dental professionals providing home-based dentistry, it may be more feasible to begin a referral-based pilot of home-based dental services within an established primary care program.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty‐nine articles examined the scope of HBPC care delivery practice or evaluated HBPC care delivery models 4,13–34 …”
Section: Resultsmentioning
confidence: 99%
“…Five studies addressed the provision of mental health care within HBPC practices. [30][31][32][33][34] Reckrey et al captured the prevalence of mental illness among patients at an urban HBPC practice where 26% of patients were diagnosed with depression, 10% had anxiety disorders, and prevalence of pharmacologic treatment for these disorders was high (26% selective serotonin reuptake inhibitors, 21.5% antipsychotics). Researchers used these data to pilot an in-home psychiatry consultation service.…”
Section: Subspecialty Services Within Hbpcmentioning
confidence: 99%